Evaluasi Kematangan Manajemen Perubahan TI Menggunakan COBIT 2019 Domain BAI07 - Mia Hamzani Dianasari; Sudin Saepudin; Hendri Ekasatria; Mupaat (Jurnal Algoritma, 2026)
The website sukabumiupdate.com, as a high-traffic online media platform, routinely performs system updates, server migrations, and feature enhancements to maintain service speed and stability. These activities may pose risks of service disruption if not managed through a structured IT change management mechanism, particularly in the digital media industry, which demands real-time system availability. This study aims to evaluate the maturity level of the information technology change management process at sukabumiupdate.com using the COBIT 2019 framework, focusing on the BAI07 domain (Managed IT Change Acceptance and Transitioning), which plays a crucial role in ensuring successful system change acceptance and transition. The research adopts a quantitative descriptive approach with a case study method, involving observation, interviews, and documentation with four respondents. The assessment was conducted using a questionnaire instrument based on BAI07 activities, measured through the COBIT 2019 capability level assessment. The results indicate that the change management process has reached Capability Level 5 (Optimizing) with an achievement score of 88.46%, demonstrating that the process is consistently implemented, well-documented, and oriented toward continuous improvement. These findings address the research gap regarding the application of the BAI07 domain in the online media industry and provide both theoretical contributions to IT governance studies and practical guidance for digital media organizations in enhancing the effectiveness and efficiency of IT change management.